Pengaruh Micro Teaching dan Bimbingan Guru Pamong terhadap Keterampilan Mengajar Mahasiswa Universitas Islam 45 - Mawaddatul Fitria; Laila Lutfiyatun Nisa; Anwar Fawaid; Ahmad Annuri (Turabian: Jurnal Pendidikan Islam, 2024)
The purpose of the study was to determine the perceptions of field experience students majoring in Islamic Religious Education at Islamic University 45 related to the influence of micro teaching and guidance of pamong teachers on teaching skills in various schools. This research is a quantitative descriptive research by conducting hypothesis testing. This research took place at the Islamic Education Study Programme at Islamic University 45 Bekasi. The population in this study were students of the Islamic Religious Education Study Programme at Islamic University 45 class of 2019 who had passed the micro teaching course and had carried out PPL, totalling 183 students. The sample taken was 37 students using proportional random sampling technique. The data collection technique is the questionnaire and documentation method. Data analysis techniques used to test the hypothesis are correlation and multiple regression analysis. The results showed that there was a positive influence of micro teaching and guidance of student teachers on teaching skills of Islamic Education Study Programme students at Islamic University 45.